2020
DOI: 10.3892/ijmm.2020.4498
|View full text |Cite
|
Sign up to set email alerts
|

Expression and clinical significance of circular RNAs hsa_circ_0000175 and hsa_circ_0008410 in peripheral blood mononuclear cells from patients with rheumatoid arthritis

Abstract: circular RNAs (circRNAs) are a novel class of RNAs that may be used as biomarkers in clinical blood samples. However, the role of circRNAs in rheumatoid arthritis (RA) has not been extensively investigated. In the present study, six circRNAs, including hsa_circ_0082689, hsa_circ_0087798, hsa_circ_0000175, hsa_circ_0008410, hsa_circ_0049356 and hsa_circ_0032959 levels were determined in peripheral blood mononuclear cells (PBMcs) collected from 24 patients with RA and 24 healthy controls (Hc) by reverse transcri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 34 publications
3
13
0
Order By: Relevance
“…53 It has been reported that the expression of circRNA_09505 was positively associated with ESR and CRP levels in serum from RA patients. 30 Additionally, circ_0001200 levels 13 and circ_0008410 52 were positively associated with silk time, while circ_0008360 level 13 was negatively associated with the silk time. The results of correlation analysis indicated that these circRNAs may play critical roles in the pathogenesis mechanism of RA and be used as a biomarker of disease severity.…”
Section: Diagnostic Potential Of Circrnas In Ramentioning
confidence: 95%
See 1 more Smart Citation
“…53 It has been reported that the expression of circRNA_09505 was positively associated with ESR and CRP levels in serum from RA patients. 30 Additionally, circ_0001200 levels 13 and circ_0008410 52 were positively associated with silk time, while circ_0008360 level 13 was negatively associated with the silk time. The results of correlation analysis indicated that these circRNAs may play critical roles in the pathogenesis mechanism of RA and be used as a biomarker of disease severity.…”
Section: Diagnostic Potential Of Circrnas In Ramentioning
confidence: 95%
“…Accordingly, Luo et al investigated the predictive power of two circRNAs (circ_0000175 and circ_0008410) in PBMCs as a holistic panel for RA diagnosis. 52 The results showed the combined area under the ROC curve was 0.971, with 93.10% sensitivity and 93.33% specificity. Similarly, combined AUC for both circ_104871 and circ_003524 was 0.855, slightly higher than that of circ_10487 (AUC = 0.833).…”
Section: Diagnostic Potential Of Circrnas In Ramentioning
confidence: 97%
“…However, the etiology and precise pathogenesis of RA remain to be fully elucidated. Substantial research has discovered that circRNAs, such as hsa_circ_0035197, hsa_circ_0000175, hsa_circRNA_104194, hsa_circ_0001200, hsa_circ_0000396, and hsa_circ_0130438, are clearly dysregulated in RA (59)(60)(61)(62)(63). It is worth noting that hsa_circ_0002715 was correlated with the joint pain score, the joint swelling score, RF, and anti-imine protein antibodies (60).…”
Section: The Role Of Circrnas In Rheumatoid Arthritismentioning
confidence: 96%
“…The levels of circ_0000175 and circ_0008410 correlated with anti-citrullinated protein antibodies and tender joint count, respectively, suggesting their expression may improve the diagnostic accuracy for RA. Thus, the expression levels of the circ_0000175 and circ_0008410 correlate with disease activity and severity [ 56 ]. These results corroborate the role that circRNAs may exhibit in the regulation of expression of target pathways that influence the occurrence and development of RA.…”
Section: Role Of Ncrnas In Rheumatoid Arthritismentioning
confidence: 99%